Integration of Kano Methods and Quality Function Deployment (Qfd) for Multi-Function Wardrobe Product Development - Rangga Kurniawan Budianti; Rony Prabowo (Universitas Muhammadiyah Sidoarjo, 2019)
In the industrial environment, there are more and more rooms that are rented out for workers and families, and the cupboard is one of the products that is often needed is a cupboard. Storage aids should be designed for safe, comfortable, ergonomic, and aesthetic use. Multi-functional wardrobes are an important aspect of storage and space-saving work. Multi-functional wardrobe designs have developed, both in terms of form and function. However, along with the development of the times, there are demands for additional functions from existing multi-functional cabinets. Based on this background, this study aims to design and manufacture multi-functional wardrobe products according to consumers' requirements. For this research's success, the Kano method and the Quality Function Deployment (QFD) are used. The results obtained show 18 attributes (customer requirements) and 18 attributes (technical response) technical parameters implemented in a multi-functional wardrobe product design. The addition of functions to this multi-functional wardrobe product is a wardrobe with 2 (two) functions and 1 (accessories) additional in one product, which can be used as a cupboard, table, and table along with a chair. In operation, it is effortless because it has a knock-down system (can be folded). When used as a table, there are chairs on the right and left sides of the cabinet door that can be removed.